Effect of curing on the hygrothermal behaviour of epoxy and its carbon composite material. (December 2020) - Rajaram, Attukur Nandagopal; Gin Boay, Chai; Srikanth, Narasimalu
Abstract: The effect of curing and ageing temperature on the moisture absorption behaviour of the epoxy and its carbon fibre composite material is investigated. The epoxy and the composite specimens were fabricated with equal volume, and their moisture uptake was measured at two different curing conditions (room and post-cured) and ageing temperatures (24⁰C and 60⁰C). The diffusivity constant and the moisture equilibrium content of the epoxy resin and its composite for all the cases are compared and discussed. The study concludes that post-curing the pure epoxy significantly increased the moisture equilibrium content irrespective of the ageing temperature, whereas the moisture equilibrium content of the post-cured composite specimen increased only at the high-temperature ageing. Room cured epoxy specimens experienced an increase in the glass transition temperature when aged at a higher temperature; surprisingly, it did not lead to an increase in the moisture absorption. Highlights: Moisture absorption comparison study on epoxy and its carbon fibre composite. Post-curing increases the diffusivity constant of both the epoxy and composite. Post-curing decreases the moisture equilibrium content of epoxy at low temp ageing. Regarding moisture induced degradation, epoxy is much critical than its composite.